Agricultural market construction: a study in Northern Extreme Cooperative - Camara, Simone; Lago, Adriano; dos Santos Amorim, Gabrieli; Pietrobelli, Valeska; Andreatta, Tanice; Spanevello, Rosani Marisa (Cooperativismo & Desarrollo, 2021)
Introduction: The objective of this paper is to investigate the role of the Far North Family Farming Mixed Cooperative in the production and supply of food from family farms in the municipality of Alpestre and region.Methodology: This is an exploratory study and a qualitative approach, structured from a case study. The in-formation was collected through an interview conducted in September 2018, conducted by a semi-structured script that contained questions ranging from the founding of the cooperative to the marketing channels ac-cessed by it.Results: It is emphasized the fundamental role of the National School Feeding Program (PNAE) represents for the cooperative, in terms of institutional market and marketing channel, considering that it is responsible for most of the production flow, and enables the increased production due to demand driven through the program.Conclusions: The study contributes to reinforce the importance of agricultural cooperatives for family farming, and when accompanied by effective public policies, promote the development of farmers, especially in relation to employment and income, as well as the region, as it stimulates economic development. and social. However, there are difficulties regarding the delivery days in the institutions and limitations between the cooperative’s desired production system and the farmers’ production system. .